The impact of educational attainment on early childbearing an instrument variable profit (IVP) analysis - Mauricio, Kim Allison G. (School of Economics, University of the Philippines Diliman, 2019)
This paper aims to investigate the relationship between educational attainment and the likelihood of experiencing an early childbirth. The study intends to aid policy_makers in making decisions regarding the importance of education as a deterrent to the prevalence of early pregnancy among adolescents. Due to the presence of an endogeneity problem that might bias the result we propose an empirical approach based on instrumental variables to deal with this problem. Data for five survey rounds from the Cebu Longitudinal Health and Nutrition Survey (CLHNS) were employed. 903 female index children aged 21 and below were included in the sample. Our analyses control for possible confounding factors, including individual and family background characteristics, and state economic conditions. Our results suggest that, female children with higher level of educational attainment have a lower likelihood of experiencing an early childbirth. We, therefore, conclude that retaining the female children and adolescents in schools will lessen their probability of getting pregnant at a young age.